Re-Examining the ‘Culture of Silence’ Through Peer-Based Pasifika Pedagogies in a New Zealand Tertiary Environment - Boon-Nanai, JM; Manuel, T; Lagolago, W; Lefono, T; Zaveri, V; Seleni, S; Ponton, V (Informa UK Limited, 2022)
This paper draws on a study that examined the experiences of four high-achieving Pasifika physiotherapy degree level students to identify factors contributing to their success. As peer students, they identified five approaches that assisted them to become high achievers within the tertiary environment. This paper refers specifically to these approaches as peer-based Pasifika pedagogies (PbPP) and broadly as culturally responsive practices. The aim of this paper is to examine how Pasifika pedagogies, such as PbPP provide culturally responsive practices that can address the ‘culture of silence’ while promoting the vā relationality, the cultural nuances and norms of their worldview as well as aligning it with modern pedagogies or tools to enhance success among Pasifika students in the New Zealand tertiary education context.
Keywords: Culture of silence; New Zealand tertiary education; Peer-based; Pasifika pedagogies; vā relationality